Berthe Morisot - Higonnet, Anne, 1959- (University of California Press, 1995)
Of the six Impressionist painters whose first exhibition scandalized and fascinated Paris in 1874, Berthe Morisot was the only woman. She reached a pinnacle of artistic achievement despite the restraints society placed on her sex, adroitly combining her artistic ambitions with a rewarding family life. Anne Higonnet brings fully to life an accomplished artist and her world.
Originally published: New York : Harper & Row, 1990.
Keywords: Morisot, Berthe, -- 1841-1895.; Morisot, Berthe, -- 1841-1895; Artists -- France -- Biography.; Human rights.; Ethnic groups.; Medical personnel.; Social psychology.; Psychology, Applied.; Social sciences.; Mental health services.; Health services administration.; Diseases.; Social problems.; Humanities.; Crime.; Social control.; National health services.; Obstetrics -- Surgery.; Reproductive technology.; Mental illness.; Criminology.; Sociology.; Philosophy.; Medical care.; Anatomy.; Pregnancy -- Complications.; Race.; Therapeutics.; Economics.; Surgery, Operative.; Steroids.; Polycyclic compounds.; Drugs.; Prejudices.; People with disabilities.; Eugenics.; Violence.; Women's rights.; Contraception.; Drug abuse.; Drug addiction.; Women's health services.; Mifepristone.; Physicians.; Women.; African Americans.; Politics, Practical.; Pregnant women.; History.; Pregnancy.; Psychology.; Government aid.; Federal aid.; Abortion.; Fetus.; Ethics; Behavioral Sciences; Human Rights; History, Modern 1601-; Ethnicity; Health Personnel; Community Health Services; Financing, Organized; Prenatal Injuries; Psychology, Social; Psychology, Applied; Social Sciences; Mental Health Services; Patient Care Management; Disease; Social Problems; Humanities; Reproduction; Social Control Policies; Persons.; Black People; Crime; Embryonic Structures; Social Control, Formal; Health Services; Estrenes; Obstetric Surgical Procedures; Social Control, Informal; Chemicals and Drugs.; Reproductive Techniques; Health Care Quality, Access, and Evaluation.; Mental Disorders; Criminology; Named Groups.; Sociology; Philosophy; Health Care Facilities, Manpower, and Services.; Estranes; Delivery of Health Care; Anatomy; Pregnancy Complications; Behavior and Behavior Mechanisms.; Health Care Economics and Organizations.; Reproductive Physiological Phenomena; Behavioral Disciplines and Activities.